2013
DOI: 10.1007/978-3-642-41004-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Biochemical, and Biological Behaviors of Vanadate and Its Oligomers

Abstract: Vanadate is widely used as an inhibitor of protein tyrosine phosphatases (PTPase) and is routinely applied in cell lysis buffers or immunoprecipitations of phosphotyrosyl proteins. Additionally, vanadate has been extensively studied for its antidiabetic and anticancer effects. In most studies, orthovanadate or metavanadate was used as the starting compound, whereas these "vanadate" solutions may contain more or less oligomerized species. Whether and how different species of vanadium compounds formed in the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…As shown in Table , compared to the wild-type enzymes, hCDC14A F48A and hCDC14B F85A mutants displayed reduced sensitivity toward compound 15 , resulting in IC 50 values that were 27.3- and 15.6-fold higher, respectively. To ascertain that this diminished effectiveness of compound 15 could be attributed to the absence of the π–π interaction, we also assessed the IC 50 of vanadate (a known general phosphate mimicking PTP competitive inhibitor , ), PhFP, and compound 9 (both PhFP and compound 9 are not supposed to engage the P+1 pocket) for the hCDC14A F48A and hCDC14B F85A mutants. As anticipated, the IC 50 values of these compounds for the hCDC14A F48A and hCDC14B F85A mutants were comparable to those observed with the corresponding wild-type enzymes (data shown in Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table , compared to the wild-type enzymes, hCDC14A F48A and hCDC14B F85A mutants displayed reduced sensitivity toward compound 15 , resulting in IC 50 values that were 27.3- and 15.6-fold higher, respectively. To ascertain that this diminished effectiveness of compound 15 could be attributed to the absence of the π–π interaction, we also assessed the IC 50 of vanadate (a known general phosphate mimicking PTP competitive inhibitor , ), PhFP, and compound 9 (both PhFP and compound 9 are not supposed to engage the P+1 pocket) for the hCDC14A F48A and hCDC14B F85A mutants. As anticipated, the IC 50 values of these compounds for the hCDC14A F48A and hCDC14B F85A mutants were comparable to those observed with the corresponding wild-type enzymes (data shown in Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…However, rats all died when they received vanadyl sulfate for more than 2 mM/kg of their body weight [ 83 ]. The biological effects are different according to the species of vanadium compounds [ 84 ]; the toxicities of vanadium in different oxidation states were divergent as well. Studies have illustrated that the highest oxidated valence (+5) of vanadium was the most toxic state [ 85 ].…”
Section: The Advance Of Applying Vanadium In Ad Treatmentmentioning
confidence: 99%
“…In addition, it was found that elevated vanadium uptake could affect cholesterol and triglyceride metabolism, and stimulate hepatic glucose oxidation and glycogen synthesis [ 27 ]. However, the toxicity of vanadium was also observed in animal experiments [ 28 , 29 ], though the biological effects may be different dependent on the species of vanadium compounds formed in the biological media [ 30 ]. Rats would all die when they were treated with vanadyl sulfate at levels greater than 2 mM V kg −1 body weight [ 31 ].…”
Section: The Pharmacological Research Of Vanadium Compounds In Treating Diabetesmentioning
confidence: 99%